MDAONTO: UMA ABORDAGEM MDA BASEADA EM ONTOLOGIA - Pinto, George Pacheco (2010)
The search for improvements in software development has driven the emergence of new technologies, paradigms, approaches that improve quality and reliability of the software product. Thus, Model Driven Development (MDD), specifically Model Driven Architecture (MDA) - a standard maintained by the Object Management Group (OMG) - appears as an option that aims to change the focus of a code-centered development to a model-centered development, aiming to achieve higher levels of abstraction and hence boost the increase of reuse, productivity and quality of the generated software. Parallel to this movement, the Semantic Web has taken shape and brought with it the use and creation of ontologies, which represents an efficient mechanism for sharing and reusing knowledge. Ontologies can map consensual knowledge about a given domain. In a MDA context a domain model is known as Computation Independent Model (CIM) and has conceptual similarities with domain ontologies. In this sense, this work aims to present/examine a proposal for the intersection between these two worlds, from this point of junction (CIM model), i.e., the focus is to present/develop an approach that uses ontologies as source artifacts in the conception of software models. Thus, we present MDAOnto, an MDA approach, a, which uses preexisting domain ontologies (written in OWL), as an initial source in the conception of software models (CIM and PIM later). Finally, this work also describes a tool that implements the proposal, as well as, an illustrative use scenario, presenting a context in which MDAOnto can be useful.